Characterization of Functionalized Polyurethane Foam for Lead Ion Removal from Water - Subhashini Gunashekar; Nidal Abu-Zahra (International Journal of Polymer Science)
Polyurethane foams functionalized with sulfonic acid groups are used in this study to exchange lead (Pb2+) ions from aqueous solutions. Toluene-2, 4-diisocyanate, 2,6-diisocyanate (TDI) was reacted with Polypropylene glycol 1200 (PPG) in 2 : 1 molar ratio to form a linear prepolymer. The linear prepolymer was further polymerized using N,N-bis(2-hydroxyethyl)-2-aminoethanesulfonic acid (BES), which acts both as a chain extender and an ion-exchanger for Pb2+ ions. The functionalized polyurethane foam was characterized by Fourier transform infrared spectroscopy (FTIR), gel permeation chromatography (GPC), scanning electron microscopy (SEM), and energy dispersive X-ray spectroscopy (EDX). The Pb2+ ion exchange capacity was determined using an Inductively Coupled Plasma Mass Spectrometer (ICP-MS). The maximum Pb2+ ion exchange capacity of the foam was found to be 51 ppb/g from a 100 ppb Pb2+ solution over a period of two hours. In addition, pH analysis was carried out on the foam composition with the best Pb2+ ion removal capacity. The pH results based on two-hour exposures showed that the functionalized polyurethane foam performed better at lower pH levels.